Torrefaction of Palm Kernel Shell Into Value-Added Solid Fuels - Mohd. Amin bin Aziz Jaafar, Mohd. Amin (Universiti Teknologi Petronas, 2011)
The use of renewable energy sources is becoming increasingly necessary due to the impacts of global warming from fossil fuel usage. Wood and other forms of biomass including energy crops and agricultural and forestry wastes are some of the main renewable energy resources available to provide liquid, gaseous and solid fuels. However, several major weakness of biomass, limit its wider application in energy generation i.e. low heating value, high moisture content, hygroscopic nature, smoke during combustion, low energy density, and low combustion efficiency. Torrefaction can help to overcome the limitations of biomass to be a more efficient energy sources. Malaysia was the second largest producer of oil palm waste, and thus palm kernel shell (PKS) has been selected to be a biomass that will be used in this study because of its good availability which is about 4.5 million tonnage-wet/year. PKS has a good potential as a fuel because of its carbon neutrality, low moisture content and high calorific value. This project aims to investigate the fundamental of torrefaction to improve the properties of PKS as a solid fuel. A study towards torrefaction of PKS will be done under varying temperature and residence time of 240, 260, and 280oC and 30, 60, and 90 minutes respectively. The changes of the torrefied PKS were characterized by the mass yield, energy yield, elemental composition analysis, calorific value analysis and proximate analysis. The mass and energy yield changes of torrefied PKS was shown to prove that the temperature has more effect compare to residence time in torrefaction. The C contents of torrefied PKS increase while H and O contents decrease, thus C:C bond proportion of the torrefied PKS increased which resulted in higher calorific value. The higher heating value (HHV) of torrefied PKS increased in the range of 5-16%. The ash and fixed carbon content of torrefied PKS increased, while the moisture and volatile matter decrease.